Analisis Penerapan Sistem Informasi Akuntansi Penjualan Kredit Pada Graha Insan Surya (GIS) Maumere - Desiderata Bengan Hulun; Maria Nona Dince; Pipiet Niken Aurelia (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to analyze the application of accounting information systems to credit sales at Graha Insan Surya (GIS) Maumere. The analysis method used in this research is qualitative method. In this study the types of data used are primary data and secondary data. Data collection in the form of documentation, observation and interviews with related parties regarding the Accounting Information System for credit sales. The results of the research obtained from the credit sales accounting information system at Graha Insan Surya (GIS) Maumere are still not effective where there are still multiple functions, namely the retail supervisor is held concurrently by cashier 1, in documents there are only requirement sheets and notes but some documents are not used in credit sales but are in accordance with company needs such as Bill of Lading, Packing Slip, Warehouse Copy, Sales Order Follow-up Copy, Cross-index file copy, Costumer copies, Account Receivable Copy, Analysis Copy, and Sales person copy. For records, there are only sales journals that are recorded manually in the Microsoft Office Excel application, flowcharts that have not been made, and an internal control system that has not run smoothly.